Four methylation-driven genes detected by linear discriminant analysis model from early-stage colorectal cancer and their methylation levels in cell-free DNA - Zhan, Lei; Sun, Changjian; Zhang, Yu; Zhang, Yue; Jia, Yuzhe; Wang, Xiaoyan; Li, Feifei; Li, Donglin; Wang, Shen; Yu, Tao; Zhang, Jingdong; Li, Deyang (Frontiers in Oncology, 2022)
The process of colorectal cancer (CRC) formation is considered as a typical model of multistage carcinogenesis, in which aberrant DNA methylation plays important roles. In this study, 752 methylation-driven genes (MDGs) were identified by MethylMix package based on methylation and gene expression data of CRC in TCGA. Iterative recursive feature elimination (iRFE) based on linear discriminant analysis (LDA) was used to determine the minimum MDGs (iRFE MDGs) which could distinguish cancer and cancer-adjacent tissues. Further analysis indicated that the changes of methylation levels of the 4 iRFE MDGs, ADHFE1-Cluster1, CNRIP1-Cluster1, MAFB and TNS4, occurred in adenoma tissues, while did not occur until stage IV in cell-free DNA. Besides, the methylation levels of iRFE MDGs were correlated with the genes involved in the reprogramming process of somatic cell to pluripotent stem cell, which is considered as the common signature of cancer cell and embryonic stem cell. Above results indicated that the 4 iRFE MDGs may play roles in the early stage of colorectal carcinogenesis, and highlighted the complicated relationship between tissue DNA and cfDNA.